Reinventing the Identity and Interests: Pakistan and the Middle East (1971 to 1979) - Farrukh Faheem (IDEA PUBLISHERS, 2020)
Pakistan's territorial mutilation in the 1971 war with India was the utmost military, psychological and political disaster for Pakistan. Pakistan lost its Eastern wing and more than ninety thousand soldiers, civilians, civilians, and along with the territory, all the same to India. In the prevailing uncertainty, Pakistan vigorously asserted its Islamic Identity to foster its moral, economic, and political interests to revive from the loss. It looked towards the Middle East to revive its national identity and interests' fulfilment. During the Seventies, political changes within the Middle Eastern region were also favourable and useful for promoting Islamic ideology and shared identity. There was much scope to achieve ideological, strategic, economic, and foreign policy objectives that Pakistan missed in the past. The new Pakistani civilian government under Bhutto arranged shuttle diplomacy overtures the Middle Eastern Muslim countries to convince them to help Pakistan rebuild its identity and achieve its interests. Bhutto was one of the principal architects of the newly charged Muslim unity. He skilfully and effectively used the OIC platform to guard the country's identity and interests.